Exploration of Analgesic and Antiinflammatory potential of Lagerstroemia speciosa - Amresh Gupta,Vipin K. Agrawal, Chandana Venkateswara Rao (Journal of Applied Pharmaceutical Science, 2017)
This study was designed to assess the analgesic and antiinflammatory actions of an aqueous ethanolic extract of Lagerstroemia speciosa L. (Family: Lythraceae). The analgesic investigations were carried out against two types of noxious stimuli, chemical (formalin-induced pain and acetic acid-induced writhing) and thermal (hotplate and tail immersion tests). The effects of standard drugs, aspirin and naloxone pretreatments were also studied. For antiinflammatory activities, the carrageenan-induced oedema of the hind paw of rats was used and the paw volume measured plethysmometrically 3h after injection. This was compared to a standard drug aspirin (300 mg/kg). The results were subjected to statistical analysis. The crude plant extract significantly increased the reaction time of hotplate and immersion tests. It decreased the writhings of acetic acid-induced abdominal contractions and lickings of formalin-induced pain. Aspirin had no effect on hotplate and tail immersion tests but showed an effect on writhing test. These results showed that the plant had both central and peripheral acting effects and this was confirmed by its effect on both phases of formalin-induced pain. The extract also significantly decreased the rat paw oedema volume at 200 mg/kg and above. In conclusion, Lagerstroemia speciosa has central and peripheral analgesic properties as well as antiinflammatory activities.
Keywords: Lagerstroemia speciosa,Analgesi, Antiinflammatory,Antinociceptive,Banaba.